Risk factors for mortality in critically ill patients with COVID‐19 in Huanggang, China: A single‐center multivariate pattern analysis. Issue 4 (14th October 2020) - Chen, Yinyin; Linli, Zeqiang; Lei, Yuting; Yang, Yiya; Liu, Zhipeng; Xia, Youchun; Liang, Yumei; Zhu, Huabo; Guo, Shuixia
Abstract: To date, the coronavirus disease 2019 (COVID‐19) has a worldwide distribution. Risk factors for mortality in critically ill patients, especially detailed self‐evaluation indicators and laboratory‐examination indicators, have not been well described. In this paper, a total of 192 critically ill patients (142 were discharged and 50 died in the hospital) with COVID‐19 were included. Self‐evaluation indicators including demographics, baseline characteristics, and symptoms and detailed lab‐examination indicators were extracted. Data were first compared between survivors and nonsurvivors. Multivariate pattern analysis (MVPA) was performed to identify possible risk factors for mortality of COVID‐19 patients. MVPA achieved a relatively high classification accuracy of 93% when using both self‐evaluation indicators and laboratory‐examination indicators. Several self‐evaluation factors related to COVID‐19 were highly associated with mortality, including age, duration (time from illness onset to admission), and the Barthel index (BI) score. When the duration, age increased by 1 day, 1 year, BI decreased by 1 point, the mortality increased by 3.6%, 2.4%, and 0.9% respectively. Laboratory‐examination indicators including C‐reactive protein, white blood cell count, platelet count, fibrin degradation products, oxygenation index, lymphocyte count, and d ‐dimer were also risk factors. Among them, duration was the strongest predictor of all‐cause mortality. Several self‐evaluation indicators that can simply be obtained by questionnaires and without clinical examination were the risk factors of all‐cause mortality in critically ill COVID‐19 patients. The prediction model can be used by individuals to improve health awareness, and by clinicians to identify high‐risk individuals.